2017
DOI: 10.3847/1538-4357/aa9c47
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Running Penumbral Waves Emerging in a Sunspot

Abstract: We present results from the investigation of 5 minute umbral oscillations in a single-polarity sunspot of active region NOAA 12132. The spectra of TiO, Hα, and 304 Å are used for corresponding atmospheric heights from the photosphere to lower corona. Power spectrum analysis at the formation height of Hα -0.6 Å to the Hα center resulted in the detection of 5 minute oscillation signals in intensity interpreted as running waves outside the umbral center, mostly with vertical magnetic field inclination >15°. A pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…It is assumed that the development of wavefronts can be caused by a thin magnetic structure in the umbra, including umbral dots and light bridges, where the cutoff frequency may be inherently different. It has been assumed that the waveguides of running waves are twisted into local spiral structures [14]. A model for the appearance of spiral wavefronts was proposed in relation to their propagation in radial magnetic fields [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that the development of wavefronts can be caused by a thin magnetic structure in the umbra, including umbral dots and light bridges, where the cutoff frequency may be inherently different. It has been assumed that the waveguides of running waves are twisted into local spiral structures [14]. A model for the appearance of spiral wavefronts was proposed in relation to their propagation in radial magnetic fields [15].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is observed that the wavefronts which are part of the already emerged RPWs detaches itself from the RPWs and jumps into the center of the umbra where it appears to expand radially and starts a new oscillations as shown in Fig. 1 (see Priya et al 2018 for more details). Along the edges of the wavefront, the periods of running waves show a large spread.…”
Section: Analysis Results and Discussionmentioning
confidence: 93%
“…In the horizontal direction, Felipe et al (2019) noted out that the spiral-arm structure rotates counterclockwise to the umbral-penumbral boundary and evolves into RPWs. Su et al (2016a) and Priya et al (2018) have slightly different views; they argued out that the wavefront spiral-arm structure of the umbral oscillations splits when it reaches the umbral boundary; a part returns to the umbra to excite the next round of umbral oscillations, and the other part enters the penumbral to form the RPWs. However, in sunspots with multiple umbrae, the propagation mechanism of oscillations between different umbrae, as well as the possibility of their sharing a common origin in the sub-photosphere, have not been definitively established.…”
Section: Introductionmentioning
confidence: 99%